A study of various factors associated with sexual dysfunction in males with type 2 diabetes mellitus - Jakka, Nagendar Reddy; Ramesh, Jayanthy (International Journal of Advances in Medicine, 2017)
Background: SD is very common in type 2 diabetic men. Many middle aged and older adults with diabetes are sexually active, but the rate of sexual inactivity is higher than in non-diabetic subjects. The objective of this study was to study various factors associated with sexual dysfunction in males with type- 2 diabetes mellitus. Methods: A total of 60 male type 2 diabetic subjects were studied. They were divided in to two groups, 42 subjects with SD were in one group and 18 subjects with normal sexual function were in the second group. Differences between groups were assessed for statistical significance using T-test, Mann-Whitney test and Chi-square test, where ever applicable. The data were presented as Mean±Standard deviation or percentages. Results: The prevalence of SD was 70%, ED was 93%, Orgasmic dysfunction was 38 %, 9 had HSDD (21%) and 22 had premature ejaculation (52%). The age (p = 0.335), duration of DM (p = 0.097), BMI (p = 0.717), WC (p = 0.138) were not significantly different between two groups. FPG (p = 0.000), PPG (p = 0.000) and HbA1c (p = 0.000) were significantly higher in SD group. Non-HDL cholesterol level (p = 0.001) and TG level (p = 0.021) were significantly higher in SD group. The eGFR (p = 0.150) was not significantly different between two groups. Spot urine protein creatinine ratio (p = 0.002) was significantly higher in SD group. Conclusions: It was concluded that SD is a highly prevalent problem in males with type 2 DM. ED is the most common form of SD, followed by PE, Orgasmic dysfunction and HSDD. The age, duration of DM, BMI and WC are not associated factors of SD.